Analysing Cost Implications Of Building Design Variables As Areas Of Modelling To Achieve Value For Money A Study on Selected Buildings in Surakarta and Surrounding Areas - Safiki, Ainomugisha, Dr. Moch. Solikin, Ir.H.M Nur Sahid,MM.MT (2016)
As the deployment of construction economics becomes more desirable today, studies have shown that the building project can be designed in different forms and shape with respect to its layout characteristics, each attracting different costs of construction on same usable floor area. Therefore, this study was aimed at 1) identifying the main client priorities on any building project and design variables used; 2) analyzing impact of plan shape design variable of on costs 3) making recommendations to those involved in building design development, on possible areas of cost saving and adding value for money. The methodology adopted involved a questionnaire survey designed based on a 5 pointer likert scale approach, and distributed among 30 respondents in areas of Surakarta, consisting of 23 consultants and 7 clients and then study case analysis of two cases i.e. case A and B, in form of hotels constructed in Jawa Tengah Indonesia. The collected data was processed using statistical methods of product moment and relative importance index, previous established building indices, then later descriptive analysis used in analyzing overall and elemental costs effects of plan shape, expressed in cost/m2 GFA. The results obtained were, clients highly demand for a design maintained in its budget cost, its quality and aesthetic, with design variables of building plane shape, building complexity and building façade as the mostly used. On the other hand the shape closet to a square was the cheapest, i.e. 1,246,551.3 rp/m2 for case B, 1,518,147.53Rp/m2 GFA for A, a 9.8% difference. The block walling was most varied in its elemental cost/m2 GFA by 38.7%. Lastly, author recommends that designers should try as possible to design a form close to square, since the wider the building shape layout, the more cost effective it becomes i.e. in terms of reducing on materials especially walling, associated finishes.